THE IMPACT OF CLIMATE CHANGE ON COASTAL TOURISM DESTINATION: CASE OF KUTA BEACH, BALI, INDONESIA - Alhilal Furqan; Fabian Indra Winandi (ASEAN Journal on Hospitality and Tourism, 2018)
Tourism is one of the strategic economic sectors in Indonesia that uses a lot of nature. Tourism destination is greatly affected by natural conditions and its changes. This study aims to identify the impact of climate change on coastal tourism destination from the perspective of stakeholders in Kuta Beach, Bali. This study employs mix methods, quantitative and qualitative. Quantitative methods employed to observe the perspective of tourists through questionnaire surveys with descriptive statistical analysis. While, the qualitative method use interview data and observation to observe the perspectives of the remaining stakeholders, namely the local government, tourism entrepreneurs, and the leaders of the traditional villages. The results show that tourists' awareness of climate change is quite high, although understanding of climate change tends to be 'normal'. Climate change variables that affect the tourist experience of Kuta Bali tourists are more related to safety, except related to sudden and extreme weather changes. This study is expected to increase the awareness of tourism stakeholders on climate change so that climate change adaptation measures can be carried out that help develop tourism.